2014
DOI: 10.1111/jnc.12734
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional interactions between NOX2‐type NADPH oxidase and the F‐actin cytoskeleton in neuronal growth cones

Abstract: NADPH oxidases are important for neuronal function but detailed subcellular localization studies have not been performed. Here, we provide the first evidence for the presence of functional NOX2-type NADPH oxidase complex in neuronal growth cones and its bidirectional relationship with the actin cytoskeleton. NADPH oxidase inhibition resulted in reduced F-actin content, retrograde F-actin flow, and neurite outgrowth. Stimulation of NADPH oxidase via protein kinase C activation increased levels of hydrogen perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 71 publications
5
80
0
Order By: Relevance
“…Integrins and semaphorin 3a (Sema3a) appear to be a major trigger of redox signals in the growth cones [40], [53]. In addition, Nadhp oxidases [54] and mitochondria locally modulate ROS signaling in the distal neurite and growth cone, and regulate the direction and the rate of neurite growth [55]. Using dimedone we were able to visualize such redox signals in growing cones, where PKG1 was colocalized with F-actin, and upon collapse, PKG1 redistributed from the tip suggesting a redox-dependent traffic that may direct PKG1 to its diverse phosphorylation targets.…”
Section: Discussionmentioning
confidence: 99%
“…Integrins and semaphorin 3a (Sema3a) appear to be a major trigger of redox signals in the growth cones [40], [53]. In addition, Nadhp oxidases [54] and mitochondria locally modulate ROS signaling in the distal neurite and growth cone, and regulate the direction and the rate of neurite growth [55]. Using dimedone we were able to visualize such redox signals in growing cones, where PKG1 was colocalized with F-actin, and upon collapse, PKG1 redistributed from the tip suggesting a redox-dependent traffic that may direct PKG1 to its diverse phosphorylation targets.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Aplysia neurons revealed that pharmacological inhibition of NOX using apocynin or VAS2870 reduces actin polymerization in growth cones, decreases retrograde actin flow, reduces neurite outgrowth and modifies the structure of actin in the growth cone transition zone, impairing growth cone formation (Munnamalai and Suter ; Munnamalai et al . ; Altenhofer et al . ).…”
Section: Redox Signaling In Axonal Outgrowth and Guidancementioning
confidence: 99%
“…Oxidation of actin decreases its ability to polymerize (Hung et al, 2011(Hung et al, , 2010Sakai et al, 2012;Terman and Kashina, 2013). However, inhibition of NOX reduces both the F-actin content at the growth cone and the retrograde actin flow in neurons, suggesting a crosslink between NOX and actin dynamics (Munnamalai and Suter, 2009;Munnamalai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%